Impact of COVID-19 on the Jordanian economy: Economic sectors, food systems, and households - Raouf, Mariam; Elsabbagh, Dalia; Wiebelt, Manfred (International Food Policy Research Institute, 2020)
Economic growth in Jordan potentially will come to a halt this year. This comes as a result of the COVID-19 pandemic outbreak. Government imposed an economic lockdown which restricted non-essential economic activities and people’s movement in order to contain the virus. A SAM multiplier model was used to estimate the economic impact of the lockdown and to explore potential recovery pathways for the Jordanian economy. Some of the key findings from this modeling exercise are: • National GDP is estimated to have fallen by 23 percent during the lockdown period. The services sector was hardest hit, seeing an estimated drop in output of almost 30 percent. • Food systems in Jordan are estimated to have experienced a reduction in output by almost 40 percent. • Employment losses during the lockdown were estimated at over 20 percent, mainly driven by job losses in services, followed by agriculture. • Household income fell on average by around one-fifth due to the lockdown, mainly driven by contraction in service sector activities, by slowdown in manufacturing activity, and by lower remittances from abroad. • GDP growth rates for Jordan’s economy will continue to be negative through 2020, ranging from -5.7 to -7.4 percent, depending on the speed of economic recovery. A slow pace of recovery is expected. This economic recovery offers opportunities for fostering sustainable economic transformation and structural change. Economic policies and incentives should be directed towards more economic diversification, greater resilience to withstand economic shocks, and job creation.